Impact of ambient air pollution on physical activity and sedentary behavior in China: A systematic review - An,R; Shen,J; Ying,B; Tainio,M; Andersen,ZJ; de,Nazelle A (Environmental Research, 2019)
This study systematically reviewed scientific evidence linking ambient air pollution to physical activity and sedentary behavior in China. A keyword and reference search was conducted in PubMed, Web of Science, and the Cochrane Library. Predetermined selection criteria included—study designs: interventions or experiments, retrospective or prospective cohort studies, cross-sectional studies, and case-control studies; subjects: people of all ages; exposures: specific air pollutants and/or overall air quality; outcomes: physical activity and/or sedentary behavior; and country/area: mainland China. Ten studies met the selection criteria and were included in the review. Six adopted a cross-sectional design and the remaining four adopted a prospective cohort design. Four studies assessed a specific air pollutant namely particulate matter with diameter <2.5μg/m3 (PM2.5), whereas the remaining six focused on overall air quality, defined using air quality indexes. Decline in overall air quality and increase in PM2.5 concentration were found to be associated with reduced daily/weekly duration of outdoor leisure-time and/or transportation-related physical activity such as walking but increased duration of daytime/nighttime sleeping among Chinese residents. In contrast, evidence linking overall air quality and PM2.5 concentration to sedentary behavior remains mixed and inconclusive. In conclusion, preliminary evidence indicates that ambient air pollution impacts Chinese residents’ daily physical activity-related behaviors. Future studies adopting objective measures of physical activity and a longitudinal or experimental study design are warranted to examine the impact of air pollution on sensitive sub-populations such as children, older adults and people with pre-existing conditions, and in locations outside China.